Effectiveness of a hypertension management protocol in rural Haitian adults and pregnant women - Marc-Aurel Martial; Katelin A. Everitt; Cempaka S. Martial; Allen M. Day; Marc Johnson; Geraldo Charles (Elsevier, 2023)
Background: Haiti's hypertension prevalence among adults ≥40 years of age is nearly twice that of nations in the Americas. Haiti Health Initiative (HHI) developed a hypertension management protocol for use in outreach clinics in Timo, a rural mountainous community in Haiti. This study aimed to evaluate the effectiveness of the hypertension protocol for treating adults ≥40 years of age and pregnant women with severe hypertension. Methods: This retrospective longitudinal study included 209 patients across 1148 clinic visits/encounters. De-identified medical records from 11 biannual outreach clinics between April 2014 to April 2019 were reviewed for analysis. Descriptive statistics, paired t-tests, and multilevel models were performed. The primary outcome was systolic and diastolic blood pressure measurements at each clinic visit. Findings: In the study (n = 1148 visits), hypertension and severe hypertension prevalence were respectively 79·8% and 38·4%. Multilevel models showed a decrease of 0·29 mmHg (p = 0·37) in systolic blood pressure and a decrease in diastolic blood pressure of 0·66 mmHg (p < 0·001) per visit. Individual factors and protocol adherence did not predict a reduction in blood pressure. Conclusion: Effective management of hypertension and other chronic conditions among hard-to-reach populations with limited healthcare access requires comprehensive outreach efforts that address care antecedents, structures, and processes. Although outreach clinics made treatment accessible to vulnerable populations, the protocol, which used medications with previously demonstrated efficacy, had little impact on reducing blood pressure in patients with severe hypertension.